2013
DOI: 10.1007/s10265-013-0616-9
|View full text |Cite
|
Sign up to set email alerts
|

Difference in cesium accumulation among rice cultivars grown in the paddy field in Fukushima Prefecture in 2011 and 2012

Abstract: After the accident of the Fukushima 1 Nuclear Power Plant in March 2011, radioactive cesium was released and paddy fields in a wide area including Fukushima Prefecture were contaminated. To estimate the levels of radioactive Cs accumulation in rice produced in Fukushima, it is crucial to obtain the actual data of Cs accumulation levels in rice plants grown in the actual paddy field in Fukushima City. We herein conducted a two-year survey in 2011 and 2012 of radioactive and non-radioactive Cs accumulation in ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 7 publications
2
24
0
Order By: Relevance
“…There were similarities found between 133 Cs and 137 Cs in distribution among plant parts, and in the relationship between plant uptake and exchangeable Cs contents (Tsukada et al 2002a;Kondo et al 2014). On the other hand, it was found that there were discrepancies between 133 Cs and 137 Cs in accumulations by rice varieties under the field conditions in Fukushima Prefecture, which was affected by the accident at the Fukushima Daiichi Nuclear Power Station in 2011 (Ohmori et al 2014). This discrepancy was, as the authors speculated, probably due to the difference in distribution in soil profile and availability to the rice between 133 Cs and 137 Cs, because 137 Cs had been freshly added to the soil surface, and not due to the isotopic effect.…”
Section: Control Of Cs Accumulation Based On Competitive Dynamics Betmentioning
confidence: 89%
“…There were similarities found between 133 Cs and 137 Cs in distribution among plant parts, and in the relationship between plant uptake and exchangeable Cs contents (Tsukada et al 2002a;Kondo et al 2014). On the other hand, it was found that there were discrepancies between 133 Cs and 137 Cs in accumulations by rice varieties under the field conditions in Fukushima Prefecture, which was affected by the accident at the Fukushima Daiichi Nuclear Power Station in 2011 (Ohmori et al 2014). This discrepancy was, as the authors speculated, probably due to the difference in distribution in soil profile and availability to the rice between 133 Cs and 137 Cs, because 137 Cs had been freshly added to the soil surface, and not due to the isotopic effect.…”
Section: Control Of Cs Accumulation Based On Competitive Dynamics Betmentioning
confidence: 89%
“…We found that the amount of radiocesium extracted by ammonium fertilizer increased the day after fertilization; therefore, soybean could absorb radiocesium. In addition, the ammonium and cesium ions are both univalent cations, and ammonium has been found to restrict cesium absorption in the hydroponics [9][10][11]. This study was used by soil.…”
Section: Discussionmentioning
confidence: 99%
“…This occurred because it recently became clear that potassium fertilization was effective for reducing the radiocesium concentration in agricultural crops [8,9]. Nitrogen (N) has a large effect on crop growth, and some reports have suggested that it also promotes the radiocesium absorption [10,11]. However, few studies have examined how nitrogen contributes to the radiocesium absorption in soybean apart from potassium.…”
Section: Introductionmentioning
confidence: 99%
“…The differences in radiocesium absorption between varieties have been conducted on rice (Ohmori et al 2014). In this paper, the absorption of radiocesium was studied comparing 10 varieties of soybean in Iitate Village, Fukushima Prefecture.…”
Section: Differences Between Soybean Varietymentioning
confidence: 99%